Missed Doses and Missed Appointments: Adherence to ART among Adult Patients in Uganda. (14th January 2013) - Shumba, C.; Atuhaire, L.; Imakit, R.; Atukunda, R.; Memiah, P.
Abstract : Background . Missed doses and appointments are predictors of incomplete adherence among patients on ART. The AIDSRelief model emphasizes treatment preparation and continuous treatment support for ART patients including community followup. Methods . In August 2008, a survey was conducted among patients on antiretroviral therapy (ART) (interquartile range for duration of ART = 29–46 months, median = 33 months, n = 763, age >16 years), in 15 health facilities in Uganda. Missed doses and appointments among adult patients on ART and the factors most associated with these were identified. Reasons for missed doses were also explored. Results . The survey revealed that 97% of the patients had not missed their doses in the last week while 93% had not missed their appointments in the last three months. For those who had missed their doses, the most common reasons were travel (48%) and forgetfulness (28%). There was a significant association between missing doses and missing appointments (P = 0.0004 ) and between alcohol use and missed doses (P < 0.005 ). Conclusions . The level of adherence to medication and clinic appointments for patients on ART in the study population was very high. It is important to strengthen adherence strategies at both facility and community levels to assist patients that are likely to miss their doses or appointments.